1983
DOI: 10.1002/1097-0142(19830901)52:5<824::aid-cncr2820520513>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Biclonal lgM gammopathy in a lymphoproliferative disorder

Abstract: An unusual case of an IgM producing lymphoproliferative disorder is presented. Using immunoflu‐orescent techniques, this study shows that the heavy chain is associated with kappa light chain in some cells, and with lambda light chain in other cells. This indicates the presence of two distinct malignant cell populations in this patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
1998
1998

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…(3) The pigment composition in PS II is more heterogeneous than in PS I If exciton diffusion is restricted to chlorophyll a molecules only (Pearlstein, 1964) and the chlorophyll b molecules act as antitraps (uphill energy transfer from chlorophyll a to chlorophyll b is not allowed), then the diffusion time to the PS II reaction centers may be longer in PS II than in PS I (Swenberg et al, 1976b) This type of heterogeneity effect may also produce a lower y in the more heterogeneous PS II system than in PS I, thus predicting a higher fluorescence quenching efficiency in PS I None of these effects appear to be relevant in the ps pulse quenching experiments in Figs 2-5 Campillo et al (1976a) have shown that fluorescence quenching at high pulse intensities is accompanied by a decrease in the observed fluorescence decay times If exciton quenching occurs directly on the level of the two pigment systems giving rise to the 685 and 735 nm emission bands, then the fluorescence lifetimes should decrease at both wavelengths as the intensity of the ps laser pulses is increased It is shown elsewhere, however, that while such a decrease is indeed observed at 685 nm, the fluorescence lifetime at 735 nm is relatively insensitive to the pulse intensity These results show that the exciton annihilation does not occur on the level of the PS I pigment system which gives rise to the 735 emission…”
Section: Exciton Diffusion Parameters and Their Temperature Dependencementioning
confidence: 99%
“…(3) The pigment composition in PS II is more heterogeneous than in PS I If exciton diffusion is restricted to chlorophyll a molecules only (Pearlstein, 1964) and the chlorophyll b molecules act as antitraps (uphill energy transfer from chlorophyll a to chlorophyll b is not allowed), then the diffusion time to the PS II reaction centers may be longer in PS II than in PS I (Swenberg et al, 1976b) This type of heterogeneity effect may also produce a lower y in the more heterogeneous PS II system than in PS I, thus predicting a higher fluorescence quenching efficiency in PS I None of these effects appear to be relevant in the ps pulse quenching experiments in Figs 2-5 Campillo et al (1976a) have shown that fluorescence quenching at high pulse intensities is accompanied by a decrease in the observed fluorescence decay times If exciton quenching occurs directly on the level of the two pigment systems giving rise to the 685 and 735 nm emission bands, then the fluorescence lifetimes should decrease at both wavelengths as the intensity of the ps laser pulses is increased It is shown elsewhere, however, that while such a decrease is indeed observed at 685 nm, the fluorescence lifetime at 735 nm is relatively insensitive to the pulse intensity These results show that the exciton annihilation does not occur on the level of the PS I pigment system which gives rise to the 735 emission…”
Section: Exciton Diffusion Parameters and Their Temperature Dependencementioning
confidence: 99%